An Islamic Leadership Model at Malaysian Public Higher Institutions: The Influence of Emotional Intelligence and Organizational Culture (S/O: 12921) - Shamsudin, Abdul Shukor; Sharif, Mohmad Yazam; Romle, Abd Rahim; Al-Swidi, Abdullah Kaid Naji (UUM, 2020)
In an attempt to become an excellent higher education hub in this region, the administrators need to be aware of the fact that a balance needs to be struck between physical and spiritual development. Parallel with this trend, the Ministry has given great attention on the leadership development program in public higher institutions. Previous studies on leadership were influenced by the conventional Western perspective and have proposed several approaches, namely traits, behavioral, contingency, and neo-charismatic models. In contrast, several scholars have debated that Islam as a way of life offers the most complete leadership model based on its high ethical system and teaching as laid in the al-Quran and the Prophet (PBUH) Sunnah. Previous studies also indicated effective leadership was influenced by several factors such as emotional intelligence. Another significant issue is organizational culture. Therefore, the purpose of this study is to empirically develop an Islamic Leadership model and examine the moderating effect of organizational culture on the relationship between emotional intelligence and Islamic leadership practices in public higher education institutions. The population consists of non-academic administrators in the northern region. Based on the literature, several hypotheses were developed and examined using SPSS for Windows ver. 22